The Effect of Fiber Volume Fraction on the Bending Strength of Fiber-Reinforced Composites of Oil Palm Empty Fruit Bunches - Rizky Gunawan; Agus Mujianto (Procedia of Engineering and Life Science, 2022)
In this modern era, the palm oil industry is growing, so the waste is also increasing. If the waste from the palm oil industry is not processed, it will pollute the environment. One way to process palm oil waste is to turn the empty palm fruit bunches (OPEFB) fibers into composite reinforcement. Various natural fibers can be applied to become composite reinforcement, so it is necessary to study the character of OPEFB fibers for composite reinforcement. This study will look at the effect of various volume fractions on the bending strength of the composite. The volume fraction consists of 20%, 30%, and 40% fiber. The composite is then tested for bending to determine the bending strength of the composite. The results of the tests showed that the highest bending strength value was the 30% volume fractional variation with 47.70 MPa. The 40% volume fraction variation has the lowest bending strength value of 29.53 MPa.